Redesigning an Undergraduate HRD Program With Stakeholder Guidance. (May 2017) - Beyerlein, Michael; Jones, Trez; Peck Parrott, Kelli
The Problem: Curriculum for students of human resource development (HRD) has evolved every decade and must continue this adaptive pattern to match the workplace. However, little research seems to be available to guide development of undergraduate HRD programs. Fewer than 100 publications seem to have addressed HRD curriculum. Of that group, few have focused on the undergraduate level. Consequently, this article provides an overview of the process of transforming the undergraduate curriculum for students at a major southwestern university to adapt its fit to the changing work world. The Solution: The article summarizes the process steps, the curricular changes, and the framework for continuous curriculum change for an undergraduate HRD program. Change may be incremental and continuous or punctuated by major redesign efforts. The latter require input from all stakeholders to generate a curriculum that is relevant and engaging. Details of the design process from the current case can guide other programs working on redesign, including the decision-making process, the rationale, and the choices about courses to include or modify. The Stakeholders: The procedure for preparing the plan for the curricular changes involved a wide range of stakeholders, including current students, faculty, advising staff, and alumni. Each group provided unique inputs from diverse perspectives which were integrated into the final plan. The outcome of the redesign work affected members of all the groups, such as the increased relevance of coursework for the students, the graduation of more qualified students for employers, and the empowering effect of involving faculty.